2021
DOI: 10.1121/10.0009040
|View full text |Cite
|
Sign up to set email alerts
|

Spatial reconstruction of the sound field in a room in the modal frequency range using Bayesian inference

Abstract: Spatial characterization of the sound field in a room is a challenging task, as it usually requires a large number of measurement points. This paper presents a probabilistic approach for sound field reconstruction in the modal frequency range for small and medium-sized rooms based on Bayesian inference. A plane wave expansion model is used to decompose the sound field in the examined domain. The posterior distribution for the amplitude of each plane wave is inferred based on a uniform prior distribution with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Acoustic fields in a room are usually intricate due to the boundaries and elements in the room that introduce scattering and diffraction effects. In the literature, various approaches can be found that characterise the sound field in a room, including plane wave expansions [8], modal expansions [9], sparse reconstruction reconstruction [10,11], Bayesian inference [12,13], kernel regression [14], deep-learning techniques [15,16], and others.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic fields in a room are usually intricate due to the boundaries and elements in the room that introduce scattering and diffraction effects. In the literature, various approaches can be found that characterise the sound field in a room, including plane wave expansions [8], modal expansions [9], sparse reconstruction reconstruction [10,11], Bayesian inference [12,13], kernel regression [14], deep-learning techniques [15,16], and others.…”
Section: Introductionmentioning
confidence: 99%